Pengetahuan Masyarakat terhadap Fenomena Stunting pada Komunitas Nelayan di Sumatera Barat - Alfani, Harun; Zamzami, Lucky; Syahrizal, Syahrizal (Umbara, 2025)
This research aims to describe the community's knowledge regarding the phenomenon of stunting and to analyze the factors contributing to stunting among small-scale fishing communities in the Pasia Kandang, Pasia Nan Tigo Village, Padang City, West Sumatra Province A qualitative approach was used: observation, in-depth interviews, and a literature review. The research results show that the understanding of stunting among fishing communities is still limited and is more often identified as a physical problem, such as being thin and short. This lack of knowledge impacts the ineffectiveness of stunting prevention efforts, which generally focus on increasing food consumption without considering nutritional balance. In addition, factors such as unstable income, low access to nutritious food, and inadequate dietary patterns are the main drivers of stunting potential in the area. This research highlights the importance of health education programs and policy interventions to improve awareness and access to balanced nutrition for small-scale fishing communities in the Pasia Kandang, Pasia Nan Tigo Village, Padang City.